A review of electrochemical oxidation technology for advanced treatment of medical wastewater - Zhang, Chengyu; Yu, Zhisheng; Wang, Xiangyang (Frontiers in Chemistry, 2022)
Antibiotics widely exist in medical wastewater, which seriously endanger human health. With the spread of the COVID-19 and monkeypox around the world, a large number of antibiotics have been abused and discharged. How to realize the green and efficient treatment of medical wastewater has become a hot research topic. As a common electrochemical water treatment technology, electrochemical oxidation technology could effectively achieve advanced treatment of medical wastewater. Since entering the 21st century, electrochemical oxidation water treatment technology has received more and more attention due to its green, efficient, and easy-to-operate advantages. In this study, the research progress of electrochemical oxidation technology for the treatment of medical wastewater was reviewed, including the exploration of reaction mechanism, the preparation of functional electrode materials, combining multiple technologies, and the design of high-efficiency reactors. The conclusion and outlook of electrochemical oxidation technology for medical wastewater treatment were proposed. It is expected that the review could provide prospects and guidance for electrochemical oxidation technology to treat medical wastewater.